The weight and ghrelin changes of fecal microbiota transplantation in rats: Weight-reducing after microbiota transplantation - Idiz, Cemile; Bektasoglu, Huseyin; Celikten, Mert; Nayci, Ali Emre; Okmen, Hasan; Idiz, Ufuk Oguz; Demirci, Selami; Aysan, Erhan (Progress in Nutrition, 2018)
Background: Fecal microbiota transplantation is a promising method to solve obesity. Our study’s aim was to investigate the changes of weight and ghrelin levels in obese rats receiving fecal microbiota transplantation from lean rats. Methodology: Twenty-one rats were divided into three equal groups: Group 1: Obese control group; group 2: Obese recipient group; and group 3: Lean donor group. Feces which was collected from donor group was transferred to the rats in recipient group, orally by gavage, 3 times every other day. The weight and ghrelin levels were measured from each rat at the beginning and end of the study. Results: There was statistically significant weight gain in donor group (p:0.001), but there were no statistical significant weight chances was detected in control and recipient groups (p:0.82, p:0.12, respectively). There was an increase in donor and control groups, but a decrease was observed in the recipient group at ghrelin levels. However, there was no significant difference at ghrelin levels in any groups (p:0.05, p:0.2, p:0.4, respectively). There was a significant relation in control group in weight and ghrelin changes (p:0.007), but no significant relation was detected in either recipient or donor groups (p:0.29, 0.53, respectively). Conclusion: Metabolism changes of obese rats were observed after fecal microbiota transplantation, and it was the only group that decreasing ghrelin levels.